Transformations of Social Bonds The Outline of the Theory of Social Change - Marody, Miroslawa (Peter Lang International Academic Publishing Group, 2018)
We live in times of accelerated changes - social, economic, and political - which are currently transforming most societies and areas of human life. Every day brings not only new shifts in political orders of various countries but also clearly observable metamorphoses of labour patterns, family forms, and modes through which we participate in political life, communicate, and which are related to each other. The pace of these changes and their complex mechanisms make it difficult to discern what directions they are actually taking. This book is about transformations of social bonds, the most fundamental sociological concept. It examines how these bonds are formed, how they are dissolved, and how they are forged anew. The book offers a preliminary reflection on the course and consequences of the ongoing transformations of the social order. At the same time, it invites to reconsider the foundations of sociological thinking.